Studi Retrospektif Penggunaan Obat dan Potensi Interaksi Obat Pasien Systemic Lupus Erythematosus - Siluh Putu Astini; Ni Nyoman Wahyu Udayani; Herleeyana Meriyani (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2021)
Systemic Lupus Erythematosus is a complex autoimmune disease involving multiple organs with various clinical manifestations and prognoses. The complexity of treatment and the emergence of drug-related problems demands a greater role of pharmacy in conducting pharmaceutical care. The aim of this study was to explore drug use and to identify potential drug interactions in SLE outpatients at one hospital in Denpasar. This study was a retrospective and observational study collection. The study used secondary data in medical records during January-December 2019. There were 210 SLE people consisting of 12.86% males and 87.14% women. 29.05% of the patients were aged 17-25 years. The most immunosuppressants used were methylprednisolone (48.93%), the most analgetic used was acetaminophen (88.46%). 12.10% of patients had a potentially serious drug interaction, 80.40% had a moderate and 7.5% had minor drug interaction.